Long-term Comparison of Bond Strength Between One/Two Bottle and Self/ Total-Etch Universal Adhesive Systems - Valian, Azam; Nejatifard, Marzieh (Journal of Dental School, 2021)
Objectives The aim of this study was to compare the shear bond strength and durability of one/two-bottle All-Bond Universal used in self-etch (SE) and total-etch (TE) modes on dentin discs. Methods In this in vitro study, 144 human premolars were allocated to 12 groups for use of one-bottle or two-bottle adhesive in SE and TE modes and their assessment at three time points. Dentin discs with 2 mm thickness were prepared. They were polished with 600 and 800 grit silicon carbide abrasive papers. One/two-bottle All-Bond Universal bonding agent was used in SE and TE modes in the groups. Composite resin cylinders were made by the Tygon tubes on the bonding surface and then cured . Shear bond strength was measured by a universal testing machine at 24 h, and 6 and 12 months, and the mode of failure was determined under a stereomicroscope at x10 magnification. Data were analyzed by two-way ANOVA and Bonferroni test. Results After 24 h and 6 and 12 months, the micro-shear bond strength was significantly lower in one-bottle SE compared with other groups. The two-bottle TE group showed the highest bond strength (P<0.001). In all groups, the bond strength significantly decreased at 12 months, compared with 24 h (P<0.05). Conclusion Two-bottle TE system showed higher bonding durability and bond strength compared with other groups.